First evidence of microplastics and their characterization in bottled drinking water from a developing country - Hossain, M. Belal; Yu, Jimmy; Banik, Partho; Noman, Md. Abu; Nur, As-Ad Ujjaman; Haque, Md. Rashedul; Rahman, Md. Mostafizur; Albeshr, Mohammed Fahad; Arai, Takaomi (Frontiers in Environmental Science, 2023)
Microplastics (MPs) have become pervasive in the environment, posing a threat to the environment, living organisms, and human health. Therefore, MPs have been extensively investigated in water bodies, soils, and the atmosphere. However, there is limited information about MPs contamination in drinking water sold in plastic packaging from underdeveloped countries. In this study, we analyzed water samples from 10 different common brands of bottled water to detect and characterize MPs using stereomicroscopic and FTIR techniques., and to estimate Oral consumption of MPs per capita consumption of MPswas also estimated. using stereomicroscopic and FTIR techniques from Bangladesh. Interestingly, our findings demonstrated that MPs were present in every brand. The average abundance of MPs varied from 14 ± 6.8 particles/L to 56 ± 23 particles/L, with a mean of 35 ±19 particles/L in all brands. This number of MPs in the studied country was comparatively higher than those found in other countries. MPs were found in four different shapes (fibers, fragments, films, and beads), with fibers dominating the samples (90%). MPs were sorted into eight different colors, with the transparent one accounting for about 66 % of the overall count, and 94% of the MPs were < 0.5 mm in size. Infrared spectral analysis ( FTIR) confirmed four type of polymers e. g., low-density polyethylene (LDPE), high-density polyethylene (HDPE), ethylene vinyl acetate (EVA) and polyethylene terephthalate (PETE) where LDPE and HDPE being dominant. The estimated daily intake of MPs per person was determined to be 2.63 particles, translating to a yearly intake of 960 particles/person. MPs in bottled drinking water might come from the sources of the raw water and the materials used in the packaging, which warrants additional research. As MPs in drinking water have direct exposure to human health, we should be aware of using plastic packaging for drinking water.